Long-term follow-up outcomes of laser-treated port wine stain patients: A double-blinded retrospective study - Lekwuttikarn R. (2023)
Background: Port wine stains (PWS) can be effectively treated with lasers. However, complete clearance is rarely observed, and data from long-term studies are limited. The study aimed to evaluate the efficacy and complications of long-term laser treatment in patients with PWS. Methods: We performed a 25-year double-blinded retrospective chart review of patients diagnosed with PWS who underwent laser treatment at Ramathibodi Hospital, Thailand, between June 1995 and June 2021. The scores for improvement and color were independently evaluated by two dermatologists. Results: A total of 129 patients were included. Most patients were male (70.54%). A total of 4141 laser treatment sessions were reviewed, with a median of 49 (interquartile range, 27–66) sessions per patient. A total of 1070 photographic records were reviewed. Overall, 53% of the patients achieved statistically significant (50%) improvement, after six treatment sessions. However, none of these patients achieved complete clearance. Due to the nonuniform treatments, we could not evaluate the efficacy of each laser type. However, this study illustrates the outcomes of a real-world setting in which various laser types were selected specifically for each patient to obtain the best result. Conclusions: Vascular lasers are a promising treatment for PWS. Although laser treatment is applicable to most patients, multiple treatment sessions are required to achieve excellent results.